A Review on Rotating Biological Contactors - Waqas, Sharjeel; Bilad, Muhammad Roil (Universitas Pendidikan Indonesia, 2019)
Rotating biological contactors (RBC) is a wastewater treatment process that provides a both acceptable effluent quality and organic removal efficiency at a comparatively very low costs. It is highly attractive due to simplicity of operation, low sludge production, small foot-print, low maintenance, and low operational cost. Complete nitrification/denitrification can be achieved by varying the disk submergence level and operating the process under both anaerobic/anoxic conditions in a single unit. In this review, pros and cons of RBC are discussed in detail along with the factors affecting its performances. Organic and hydraulic loading and hydraulic retention time are the main parameters followed by additional parameters such as rotational speed, media, disk submergence, dissolved oxygen level, influent and effluent characteristics, and step-feeding in affecting the performance of an RBC system. RBC has shown promising results for the removal of biodegradable matter, nitrogen and phosphorous removal. The approaches for hybridization of biological processes to improve their overall performance are also review. Such success story is assess so explore possibility of developing RBC based hybrid processes. Hybrid RBC can be form from in-combination with other processes for minimizing energy requirements and maximizing the efficiency of the system.